Analysis of polarized pulse propagation through one-dimensional scattering medium. (August 2017) - Zhang, Yong; Yao, Feng-Ju; Xie, Ming; Yi, Hong-Liang
Abstract: This paper analyzes the polarized light propagation in a one-dimensional scattering medium with the upper surface subjected to an oblique incident short-pulsed laser beam using the natural element method (NEM). The NEM discretization scheme for the transient vector radiative transfer equation (TVRTE) is presented in detail. The accuracy of the natural element method for transient vector radiative transfer in the scattering medium is assessed. Numerical results show that the NEM is accurate, and effective in solving transient polarized radiative problems. We examine a square short-pulsed laser transport firstly in the atmosphere with Mie scattering and then within aerosol scattering medium. We then investigate the transient polarized radiative transfer problem in the atmosphere-ocean system. The time-resolved signals and the polarization state of the Stokes vector are presented and analyzed. It is found that the scattering types of the medium make greatly influence on the transient transportation of the polarized light. Critically, the polarization states of the backward and forward scattered photons show significantly different time varying trends. For the two-layer system with dissimilar refractive index distributions, due to the total-reflection effect, the existence of a Fresnel interface significantly changes the polarization state of the light, and discontinuous distribution features are observed on the interface. Highlights: Transient vector radiative transfer in 1D scattering medium is solved by NEM. A square short-pulsed laser transport in Mie or aerosol scattering medium is examined. The atmosphere-ocean layer with Fresnel interface is considered. The time-resolved signals and the polarization state of the lights are analyzed.